Development of markers and crop improvement programmes - Samiullah Khan, Mohammad Imran Kozgar, Neelofar Jabeen (Recent Research in Science and Technology, 2009)
The development of markers for genetic analysis of different plant species, for monitoring the variations in and among species, to create new source of genetic variations by introducing new and favorable traits from landraces and related species, to develop the evolutionary tree among plant species and more importantly to increase the production of crops is painstaking efforts of plant breeders started from initial years of last century. Improvement in marker detecting systems and in the techniques used to identify markers linked to useful traits -Marker assisted selection (MAS) and Quantitative trait loci (QTL) - has enabled great advancements in recent years and can be utilized for more advanced research in future. Identification of markers linked to useful traits is based on complete linkage maps which helped to understand the basics of epistasis, pleiotropy and heterosis. . While morphological markers have been the basics of most work in marker development system but presently the molecular markers like RFLP (restriction fragment length polymorphism), RAPD (random amplified polymorphic DNA), and AFLP (amplified fragment length polymorphism) has generated the valuable marker systems. SNP (single nucleotide polymorphism) and SSR (simple sequence repeat) marker systems have been developed and is predicted to lead advance study by their implementation in breeding programmes. In this review emphasis has been laid on the current stage of marker development and to reveal the potential uses of supplementing the molecular and biochemical marker systems with morphological markers.